Width-dependent continuous growth of atomically thin quantum nanoribbons from nanoalloy seeds in chalcogen vapor - Li, Xufan; Wyss, Samuel; Yanev, Emanuil; Li, Qing-Jie; Wu, Shuang; Sun, Yongwen; Unocic, Raymond R.; Stage, Joseph; Strasbourg, Matthew; Sassi, Lucas M.; Zhu, Yingxin; Li, Ju; et al. (Nature communications, 2024)
Nanoribbons (NRs) of atomic layer transition metal dichalcogenides (TMDs) can boost the rapidly emerging field of quantum materials owing to their width-dependent phases and electronic properties. However, the controllable downscaling of width by direct growth and the underlying mechanism remain elusive. Here, we demonstrate the vapor-liquid-solid growth of single crystal of single layer NRs of a series of TMDs (MeX 2 : Me = Mo, W; X = S, Se) under chalcogen vapor atmosphere, seeded by pre-deposited and respective transition metal-alloyed nanoparticles that also control the NR width. We find linear dependence of growth rate on supersaturation, known as a criterion for continues growth mechanism, which decreases with decreasing of NR width driven by the Gibbs-Thomson effect. The NRs show width-dependent photoluminescence and strain-induced quantum emission signatures with up to ≈ 90% purity of single photons. We propose the path and underlying mechanism for width-controllable growth of TMD NRs for applications in quantum optoelectronics. Size control in quantum materials by direct growth is still difficult to achieve. Here, the authors present the width-dependent growth of single-layer nanoribbons of transition metal dichalcogenides from nanoalloy seeds, achieving strain-induced quantum emission with a purity of up to 90 % for single photons.